Radiation brain moms and citizen scientists : the gender politics of food contamination after the Fukushima - Kimura, Aya Hirata, 1974- (Duke University Press, 2016)
Aya Hirata Kimura traces the experiences of citizen scientists-particularly mothers-who after the 2011 Fukushima Daiichi Nuclear Power Plant disaster collected scientific data that revealed radiation-contaminated food, showing how the Japanese government used neoliberal and traditional gender ideologies to discount and socially sanction these women and their findings.